Resource efficiency and green economic sustainability transition evaluation of green growth productivity gap and governance challenges in Cambodia - Jyrki Luukkanen; Jari Kaivo‐oja; Noora Vähäkari; Tadhg O'Mahony; Mika Korkeakoski; Juha Panula‐Ontto; Jarmo Vehmas; Anh Nguyen Quoc (Wiley, 2022)
This study provides an analysis of Cambodian socio‐economic and environmental development. The analysis applies the Sustainable Society Index—database and uses Sustainability Window analyses linked to the green growth strategy in Cambodia. The novel analyses provide criteria for weak and strong sustainability and are further developed to evaluate the green growth productivity gap.
We have carried out empirical analyses using indicators of the different dimensions of sustainability—economic, social, and environmental. The Sustainability Window defines the minimum economic development for social sustainability and the maximum economic development for environmental criterion for sustainability.
This study demonstrates methodological usefulness of the Sustainability Window analysis in the fields of development studies and green growth. The methodological novelty of this study is to use Sustainability Window approach and to provide a novel empirical testbed for strong and weak sustainability analyses as well as for the analysis of the green growth resource use productivity gap.